Comparative analysis of arterial compliance in mice genetically null for cathepsins K, L, or S. (October 2022) - Omojola, Victor O.; Hardnett, Zaria; Song, Hannah; Dong, Hai; Alexander, David J.; Michael, Adeola O. Adebayo; Gleason, Rudolph L.; Platt, Manu O.
Abstract: Cysteine cathepsins are potent proteases implicated in cardiovascular disease for degrading extracellular matrix (ECM) whose structure and integrity determine the mechanical behavior of arteries. Cathepsin knockout mouse models fed atherogenic diets have been used to study their roles in cardiovascular disease, but the impacts of cathepsin knockout on non-atherosclerotic arterial mechanics are scarce. We examine arterial mechanics in several cathepsin knockout mouse lines (CatK −/−, CatL −/− ApoE −/− and CatS −/− ApoE −/− ) and controls (C57/Bl6, apolipoprotein E −/− ). Common carotid arteries of three month-old mice were isolated and underwent biaxial mechanical testing and opening angle tests. Measured wall thicknesses and pressure-diameter curves were fed into a 4-fiber constitutive model to assess differences in material properties. Pressure-diameter data revealed CatL −/− ApoE −/− arteries were smaller in caliber compared to CatK −/−, CatS −/− ApoE −/− and ApoE −/− controls and were less compliant than ApoE −/− and CatS −/− ApoE −/− arteries at lower pressures, where elastin governs the mechanical response. CatK −/− arteries showed increased in vivo axial stretches compared to CatL −/− ApoE −/− and CatS −/− ApoE −/− arteries. CatL −/− ApoE −/− arteries were less compliant than ApoE −/− and CatS −/− ApoE −/− arteries pressurized to sub-diastolic pressures. 4-fiber and unified fiber distribution models were able to capture arteries' nonlinear mechanical responses; calculated material parameters suggested that ApoE −/− arteries had increased axial parameters compared to CatL −/− ApoE −/− and CatS −/− ApoE −/− arteries. Taken together, the data suggests that loss of the potent collagenase catK increases axial and circumferential arterial compliance, while knockout of the elastase catL decreased circumferential arterial compliance, and knockout of the elastase catS showed no impact on carotid arterial mechanics.